Molecular Identification of Nocardia seriolae and Comparative Analysis of Spleen Transcriptomes of Hybrid Snakehead (Channa maculata Female × Channa argus Male) With Nocardiosis Disease - Zhang, Ning; Zhang, Hairui; Dong, Zhongdian; Wang, Wei (Frontiers in Immunology, 2022)
Hybrid snakehead (Channa maculata female × Channa argus male) is a new freshwater aquaculture fish species in southern China. During intensive aquaculture, hybrid snakeheads are often infected by Nocardia seriolae. In this study, hybrid snakehead infected suspiciously by N. seriolae in an artificial breeding pond were examined. Diseased hybrid snakeheads swam slowly without food intake, and the clinical symptoms included skin wound, anal swelling and ascites, and white granulomatous in liver, spleen, and kidney of fish. Through bacterial isolation, 16S rDNA sequencing, fluorescence in situ hybridization (FISH) and artificial infection experiment, the pathogen was identified as N. seriolae. Furthermore, the spleen samples from diseased and healthy male hybrid snakeheads in the same pond were used for RNA-Seq analysis. A total of 3,512 unique transcripts (unigenes) were identified as differentially expressed genes (DEGs), and 1,886 of them were up-regulated in diseased fish. The expression patterns of 20 DEGs were verified by quantitative polymerase chain reaction (qPCR). Several immune-related pathways and many immune-related genes were identified. qPCR results showed that the expression patterns of immune-related genes in the liver and kidney of diseased fish were comparable to that in the spleen. This study provides deep-sequencing data of hybrid snakehead spleen and will help understand the immune response of hybrid snakehead to N. seriolae. It is also helpful for the biomarker screening of fish-borne Nocardia spp. and the breeding of nocardiosis-resistant fish species.